Health Promotion in Okinawa (Japan) and Indonesia from the Perspective of Blue Zones and Healthy Longevity - Hokama, Naoki; Sato, Mayumi; Djaya, Andi Muhammad Fiqri Muslih; Tamura, Yuki; Imura, Kiyoko; Sugimoto, Hiroshi; Seto, Kiyoka (Indonesian Contemporary Nursing Journal (ICON Journal), 2025)
In March 2024, I had the opportunity to visit the city of Loma Linda, California, USA, for training. Loma Linda is a green town with a population of about 25,000, where residents exhibit a high level of health consciousness, particularly in their diet. I learned that this area has been attracting attention since around 2000 as a so-called "Blue Zone." Therefore, we will focus on the "Blue Zones," known as regions of healthy longevity, with a particular emphasis on comparing Okinawa Prefecture (Japan) and Loma Linda, California, USA. The current status and challenges of health promotion in Indonesia and future possibilities for health promotion strategies will be examined.